Influence of PTPN22 Allotypes on Innate and Adaptive Immune Function in Health and Disease - Armitage, Lucas H.; Wallet, Mark A.; Mathews, Clayton E. (Frontiers in Immunology, 2021)
Protein tyrosine phosphatase, non-receptor type 22 (PTPN22) regulates a panoply of leukocyte signaling pathways. A single nucleotide polymorphism (SNP) in PTPN22, rs2476601, is associated with increased risk of Type 1 Diabetes (T1D) and other autoimmune diseases. Over the past decade PTPN22 has been studied intensely in T cell receptor (TCR) and B cell receptor (BCR) signaling. However, the effect of the minor allele on PTPN22 function in TCR signaling is controversial with some reports concluding it has enhanced function and blunts TCR signaling and others reporting it has reduced function and increases TCR signaling. More recently, the core function of PTPN22 as well as functional derangements imparted by the autoimmunity-associated variant allele of PTPN22 have been examined in monocytes, macrophages, dendritic cells, and neutrophils. In this review we will discuss the known functions of PTPN22 in human cells, and we will elaborate on how autoimmunity-associated variants influence these functions across the panoply of immune cells that express PTPN22. Further, we consider currently unresolved questions that require clarification on the role of PTPN22 immune cell function.